TYPES OF PHRASAL VERBS IN “YOUNG SHELDON” SEASON 02 EPISODE 01 - Tambunan, Sunarti Desrieny (Asosiasi Dosen Muda Indonesia, 2024)
Phrasal verbs are the combination of a verb with one or two particles (prepositions or adverbs). Phrasal verbs have four types based on Workman’s theory (1995). Therefore, this present research is aimed at finding the types of phrasal verbs in a series entitled “Young Sheldon”, season 02, episode 01. Qualitative research is applied in order to analyze the data. The result showed that there are ten (10) phrasal verbs. Three (3) phrasal verbs that belong to type 1, five (5) phrasal verb that belong to type 2, and two (2) phrasal verbs that belong to type 4.